2020
DOI: 10.1111/1440-1681.13421
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine on postoperative gastrointestinal tract dysfunction after laparoscopic surgery for gynaecological malignancies: A randomized controlled trial

Abstract: Background The aim of this study was to compare the effects of nalbuphine and sufentanil on the gastrointestinal (GI) tract after laparoscopic surgery for gynecological malignancies. Methods A total of 100 patients aged between 18-70 years with American Society of Anesthesiologists (ASA) physical status I-II who scheduled for laparoscopic radical hysterectomy under general anaesthesia were enrolled. Patients were randomized to receive either sufentanil (Group S) or nalbuphine (Group N) to receive either sufent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Moreover, because nalbuphine has very weak reactivity with delta (δ) receptors, this drug is expected to cause reduced irritability or anxiety 5,6 . In the clinical setting, pretreatment with nalbuphine can effectively reduce propofol‐induced injection pain and propofol consumption as well as ameliorate postoperative hyperalgesia induced by high‐dose remifentanil or sufentanil 7–9 . Nalbuphine exhibits a higher therapeutic index owing to its reduced incidence of adverse events (AEs), but has analgesic effects similar to those of morphine 10 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Moreover, because nalbuphine has very weak reactivity with delta (δ) receptors, this drug is expected to cause reduced irritability or anxiety 5,6 . In the clinical setting, pretreatment with nalbuphine can effectively reduce propofol‐induced injection pain and propofol consumption as well as ameliorate postoperative hyperalgesia induced by high‐dose remifentanil or sufentanil 7–9 . Nalbuphine exhibits a higher therapeutic index owing to its reduced incidence of adverse events (AEs), but has analgesic effects similar to those of morphine 10 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The limitations in our study may cover the real outcome. However, recent studies suggested that nalbuphine did not shorten the time to the first flatus or the first defecation compared with sufentanil in patients after laparoscopic surgery for gynecological malignancies ( 25 ). Moreover, nalbuphine did not produce a worthwhile improvement in gastric emptying compared with pethidine in patients following the laparoscopic sterilization ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with μ-opioid receptor agonists such as remifentanil, sufentanil, and fentanyl, nalbuphine is a kappa-opioid receptor agonist and μ-opioid receptor antagonist with fewer side effects and a higher safety profile [ 9 , 10 ]. Nalbuphine is structurally similar to naloxone, mainly used in clinical practice for intraoperative and postoperative analgesia [ 11 , 12 ]. Some researchers reported that nalbuphine is primarily acted on kappa receptors to produce analgesia, which can be reversed by naloxone dose-dependently; when acting on μ-receptors, respiratory depression is less than morphine due to the capping effect [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%